Depression and quality of life in patients on long term hemodialysis at a nationalhospital in Ghana: a cross-sectional study - Ganu, Vincent J (Ghana Med J, 2018)
The study examined quality of life and prevalence of depressive symptoms in patients on long term hemodialysis. Further, it explored the impact of socio-demographic characteristics on depression and quality of life. DESIGN: Study design was cross-sectional. SETTING: Study was conducted in the two renal dialysis units of the Korle-Bu Teaching hospital in Accra, Ghana. PARTICIPANTS AND STUDY TOOLS: One hundred and six participants on haemodialysis were recruited for the study. The Patient Health Questionnaire and the World Health Organization Quality of Life instrument were used to assess depression and quality of life. RESULTS: Forty five percent of participants screened positive for symptoms of depression. Approximately 19% obtained low scores on overall quality of life. There were significant negative correlations between the following: Depression and overall QoL, Depression and duration of dialysis treatment and Depression and income level. There was positive correlation between overall QoL and duration of dialysis, treatment and income. CONCLUSION: Depressive symptoms were common amongst patients on long term hemodialysis. Haemodialysis patients who obtained low scores on quality of life measures were more likely to screen positive for depressive symptoms. Screening for depressive symptoms among these patients is critical as early treatment may improve their general wellbeing. FUNDING: Not indicayed